1988
DOI: 10.1007/bf00057944
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric observations of comet Hartley-Good (1985l)

Abstract: Spectrophotometric observations of Con+ Hartley-Good (19851) during five nights in 1985 are presented in the wavelength range Xh3200-7000 A. The emission bands due to CN, CH, C,, and C, molecules are observed. The abundances (N) and production rates (Q) of the molecules are derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The comets Bradfield (1980t), Austin (1982g), Kohoutek (1973f), Crommelin (1983n), P/Encke (1984) and P/Halley (1982i) observed by Goraya et al (1982;1986a, b;, 1988, Babu (1974) and Hartley-Good (19851) observed by Rautela et al (1988) were studied in the framework of the Haser model (1957) by using our recently derived fluorescence efficiencies. For completeness, we have extended our Haser model analysis to C2 (1, 0), Cz (0, l), C2 (0,2) and C3 (0, 0,O) weak emission band fluxes observed in the coma of comet Wilson (19861) by Sanwal and Rautela (1988) using our derived g-values at rh = 1 AU as described below.…”
Section: Introductionmentioning
confidence: 99%
“…The comets Bradfield (1980t), Austin (1982g), Kohoutek (1973f), Crommelin (1983n), P/Encke (1984) and P/Halley (1982i) observed by Goraya et al (1982;1986a, b;, 1988, Babu (1974) and Hartley-Good (19851) observed by Rautela et al (1988) were studied in the framework of the Haser model (1957) by using our recently derived fluorescence efficiencies. For completeness, we have extended our Haser model analysis to C2 (1, 0), Cz (0, l), C2 (0,2) and C3 (0, 0,O) weak emission band fluxes observed in the coma of comet Wilson (19861) by Sanwal and Rautela (1988) using our derived g-values at rh = 1 AU as described below.…”
Section: Introductionmentioning
confidence: 99%